The effect of intra-vaginal oxytocin on sexual function in breastfeeding mothers: a randomized triple-blind placebo-controlled trial - Arezu Mesbahi; Sakineh Mohammad-Al; Zahra Ghorbani; Mojgan Mirghafourvand (BMC, 2022)
Abstract Background Considering the importance of sexual function, high prevalence of sexual dysfunction (especially dyspareunia caused by atrophic vaginitis) in breastfeeding women, and lack of effective interventions, the present research aimed to determine the effect of oxytocin (OXT) vaginal gel on sexual function (primary outcome), sexual satisfaction, and depression (secondary outcomes) in the breastfeeding women. Methods This randomized triple-blind controlled trial was conducted on 64 breastfeeding women who referred to health centers in the city of Tabriz, Iran, in 2020-21. Participants were equally assigned to intervention/control groups using block randomization. 200 IU of OXT vaginal gel was given to the participants in the intervention group daily for eight week and the same protocol was carried out for the control group with placebo. Standard questionnaires of Female Sexual Function Index (FSFI), Edinburgh Postpartum Depression Scale (EPDS) and Sexual satisfaction scale for women (SSSW) were completed at baseline and 8 weeks after intervention. ANCOVA test was used to compare post-intervention mean score of the groups, adjusted for the baseline values. Results After intervention, there was no statistically significant difference between groups in terms of mean total score of FSFI (Adjusted Mean Difference (AMD): 1.14; 95% Confidence Interval (95% CI): -1.28 to 9.16; P= 0.349) and sexual satisfaction (AMD: 5.01; 95% CI: -0.53 to 10.56; P= 0.075). However, there was statistically significant difference between the groups in terms of mean scores of sexual contentment (AMD: 1.56; 95% CI: 0.29 to 2.83; P = 0.017) and depression (AMD: -1.90; 95% CI: -1.27 to -2.54; P < 0.001). One participant in the OXT group and one participant in the placebo group reported mild uterine contraction and one person in the placebo group reported vaginal burning sensations. Conclusions No evidence was found for the effects of OXT gel in the improvement of FSFI, even though, OXT significantly improved sexual satisfaction in the domain of contentment, and improved the symptoms of depression in comparison to the placebo group. However, a definite conclusion requires more research in this regard. Trial registration the Iranian Registry of Clinical Trials (IRCT), code: IRCT20120718010324N55 , Date of registration: 27/05/2020, URL: https://en.irct.ir/user/trial/44986/view .